Fiscal Policy and Zakat: Their Impacts on Poverty Reduction in Banten Province, Indonesia - Nursaman; Ahmad Lukman Nugraha; Ah. Fathonih; Mustofa; Surya Darma Syam; Ihksanudin (Universitas Pembangunan Nasional Veteran Jakarta, 2026)
Abstract Poverty remains a major development challenge in Indonesia, particularly at the regional level, where disparities in income distribution and access to economic opportunities persist. In addition to government fiscal interventions, zakat has emerged as an important Islamic fiscal instrument that can support poverty reduction efforts. However, empirical evidence regarding the combined contribution of fiscal policy and zakat to poverty reduction remains limited, particularly in regional contexts. This study aims to examine the impacts of fiscal policy and zakat on poverty reduction in Banten Province. This research employs a quantitative approach using panel data from five districts/cities in Banten Province during the period 2017–2021. Fiscal policy is represented by regional government expenditure (APBD), while zakat is measured through zakat collection and distribution data. The analysis employs panel data regression techniques to estimate the effects of fiscal policy and zakat on poverty reduction. The results indicate that fiscal policy has a significant effect on poverty reduction, suggesting that regional expenditure contributes to improving welfare and reducing poverty levels. Zakat also has a significant effect on poverty reduction through its role in supporting vulnerable households and enhancing social welfare. Furthermore, fiscal policy and zakat jointly strengthen poverty reduction efforts, demonstrating that public fiscal instruments and Islamic social finance can complement one another in addressing socio-economic challenges. This study contributes to the growing literature on poverty reduction by providing empirical evidence on the role of government fiscal policy and zakat in reducing poverty at the regional level. The findings suggest that stronger coordination between government expenditure programs and zakat management institutions can improve the effectiveness of poverty reduction strategies in Banten Province and other regions with similar socio-economic characteristics. AbstrakKemiskinan masih menjadi salah satu tantangan utama pembangunan di Indonesia, khususnya di tingkat daerah yang masih menghadapi kesenjangan pendapatan dan keterbatasan akses terhadap peluang ekonomi. Selain intervensi fiskal pemerintah, zakat juga memiliki potensi sebagai instrumen fiskal Islam yang dapat mendukung upaya pengurangan kemiskinan. Namun demikian, kajian empiris yang menganalisis kontribusi kebijakan fiskal dan zakat secara simultan terhadap pengurangan kemiskinan, khususnya pada tingkat daerah, masih relatif terbatas. Penelitian ini bertujuan untuk menganalisis pengaruh kebijakan fiskal dan zakat terhadap pengurangan kemiskinan di Provinsi Banten. Penelitian ini menggunakan pendekatan kuantitatif dengan data panel yang mencakup lima kabupaten/kota di Provinsi Banten selama periode 2017–2021. Kebijakan fiskal direpresentasikan oleh realisasi Anggaran Pendapatan dan Belanja Daerah (APBD), sedangkan zakat diukur berdasarkan data penghimpunan dan penyaluran zakat. Analisis dilakukan menggunakan regresi data panel untuk menguji pengaruh kebijakan fiskal dan zakat terhadap pengurangan kemiskinan. Hasil penelitian menunjukkan bahwa kebijakan fiskal memiliki pengaruh signifikan terhadap pengurangan kemiskinan melalui peningkatan aktivitas ekonomi, pelayanan publik, dan program kesejahteraan masyarakat. Zakat juga memiliki pengaruh signifikan terhadap pengurangan kemiskinan melalui peningkatan kapasitas ekonomi kelompok masyarakat berpendapatan rendah dan penguatan perlindungan sosial. Selain itu, kebijakan fiskal dan zakat secara simultan memperkuat upaya pengurangan kemiskinan, yang menunjukkan bahwa instrumen fiskal pemerintah dan instrumen fiskal Islam dapat saling melengkapi dalam mengatasi berbagai permasalahan sosial ekonomi. Penelitian ini memberikan kontribusi pada pengembangan literatur mengenai pengurangan kemiskinan dengan menghadirkan bukti empiris tentang peran kebijakan fiskal dan zakat pada tingkat daerah. Temuan penelitian mengindikasikan bahwa sinergi antara program belanja pemerintah daerah dan pengelolaan zakat yang lebih efektif dapat meningkatkan keberhasilan strategi pengurangan kemiskinan di Provinsi Banten.